Reacciones adversas medicamentosas potenciales reportadas en el Servicio de Medicina Interna -10C en el Hospital Nacional Edgardo Rebagliati Martins, octubre-diciembre 2016 - Reyes Gil, Verónica Lisette (2018)
The objective of this report was to evaluate the potential adverse drug reactions reported in the National Hospital Edgardo Rebagliati Martins in the Internal Medicine Service-10C during the months of October-December 2016, for which 25 yellow sheets of reports of adverse reactions were used. . The adverse reactions were evaluated according to age, sex, anatomical, therapeutic and chemical classification: by active principle and by therapeutic group, method of the World Health Organization by affected organs and systems, algorithm of decision of causality of the Ministry of Health and according to the classification of Rawlins and Thompson. Out of a total of 25 reports of suspected adverse reactions, 24% were from patients between 81-90 years old, 20% from 71-80 years, and a higher percentage was seen in geriatric patients; % compared to 40% of the male sex. According to the anatomical, therapeutic and chemical classification, the carbapenems were the therapeutic group that reported the most ADR with 16% followed by 8% for the group of glycopeptides, quinolones and glucocorticoids, according to the classification by organs and systems affected the greatest number of reports of adverse reactions correspond to disorders of the gastrointestinal system with 36% followed by 20% for skin disorders and appendices, according to the causality algorithm 48% are probable adverse reactions, 28% possible, 20% are defined and 4% conditional; of which 48% are serious, 36% are not serious and 16% are serious and according to the Rawlins and Thompson classification 56% are type A adverse reactions and 44% type B. It is concluded that ADRs had a higher incidence in geriatric patients, with gastrointestinal disorders being the most frequent